(untitled) (Global Journal of Science Frontier Research, 2014)
The exp(-‘ (»))-expansion method is used as the first time to investigate the wave solution of the nonlinear Burger equation with power law nonlinearity, the perturbed non-linear Schrodinger equation with kerr law nonlinearity. The proposed method also can be used for many other nonlinear evolution equations.